2021
DOI: 10.3390/antiox10050778
|View full text |Cite
|
Sign up to set email alerts
|

Hidrox® Counteracts Cyclophosphamide-Induced Male Infertility through NRF2 Pathways in a Mouse Model

Abstract: Background: Every year, men use cyclophosphamide to treat various cancers and autoimmune diseases. On the one hand, this chemotherapy often has the beneficial effect of regressing the tumor, but on the other hand, it leads to infertility due to excessive oxidative stress and apoptosis in the testes caused by its metabolite, acrolein. Methods: The objective of this study was to evaluate the beneficial power of a new compound called Hidrox®, containing 40–50% hydroxytyrosol, in counteracting the damage related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 118 publications
0
37
0
Order By: Relevance
“…Much evidence supports the role of oxidative stress in the progress of FM [5,49]. Hidrox ® is known to influence the promotion of the transcription of genes downstream of Nrf2 activation [22]. Nrf2 represents a key regulator of cellular antioxidant response [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much evidence supports the role of oxidative stress in the progress of FM [5,49]. Hidrox ® is known to influence the promotion of the transcription of genes downstream of Nrf2 activation [22]. Nrf2 represents a key regulator of cellular antioxidant response [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, one of the main components of the Mediterranean diet is olive oil, and the main phytochemical contained in it is hydroxytyrosol (HT) [19]. Hydrox ® (HD), which contains 40-50% HT, has been described as a free-radical scavenger and an antioxidant with important antimicrobial, anti-inflammatory, and neuroprotective properties [20][21][22][23][24]. Due to the biological properties of HT and its safety profile [25], the focus of our study was to investigate whether HD was able to modulate nociception, microglia activation, and oxidative stress, using an FM-like model induced by reserpine injections.…”
Section: Introductionmentioning
confidence: 99%
“…Sesamin commonly induces hormetic dose responses in numerous biological models as endpoints of biomedical and clinical relevance. For example, sesamin can prevent neurodegeneration related to the accumulation of oxidative stress by regulating the Nrf2-ARE pathway ( Fusco et al, 2021 ; Le and Inoue, 2021 ). The Nrf2-ARE axis plays a key role as an important signal to protect cells from endogenous and exogenous oxidative stress ( de Freitas Silva et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“… 15 , 16 Therefore, their potential as preventive agents against chemotherapy-induced toxicities cannot be over emphasised. 17 Emodin (EMD) is a bioactive naturally occurring anthraquinone found in several plant and fungal species, and it has been reported to have several biological properties including antineoplastic, antioxidant, anti-inflammatory, antidiabetic, hepatoprotective and anti-angiogenic properties. 18 Previous studies have reported the protective properties of emodin against cisplatin-induced nephrotoxicity, while another study suggested that emodin showed hepatoprotective effects against CCl 4 -induced hepatic injury in rats via antioxidant effects.…”
Section: Introductionmentioning
confidence: 99%